2004
DOI: 10.1055/s-2004-813220
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Different Cardiac MRI Sequences at 1.5 T/3.0 T with Respect to Signal-to-Noise and Contrast-to-Noise Ratios - Initial Experience

Abstract: In all cardiac FSE sequences, SNR and CNR at 3.0 T were found to be increased compared to 1.5 T without any major changes of the sequence parameters. The adjusted SSFP sequences fulfilled the expected increase in SNR at 3.0 T but showed no increase in CNR. On the contrary, the overall image quality did not change or was even found to be significantly lower for the SSFP and the FSE sequences at the free wall of the RV. Nevertheless, the results are encouraging for the use of 3.0 T for cardiac tissue characteriz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
46
0
5

Year Published

2004
2004
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(53 citation statements)
references
References 7 publications
2
46
0
5
Order By: Relevance
“…Cardiac imaging at 3.0 T has demonstrated the potential for significant improvement in signal-to-noise ratios (SNR) and image quality [24,25], but may be associated with greater B 1 and B 0 field inhomogeneities, longer T1 relaxation and power deposition limitations [26]. Multiecho imaging of the heart therefore poses a number of challenges at high field strength.…”
Section: Discussionmentioning
confidence: 99%
“…Cardiac imaging at 3.0 T has demonstrated the potential for significant improvement in signal-to-noise ratios (SNR) and image quality [24,25], but may be associated with greater B 1 and B 0 field inhomogeneities, longer T1 relaxation and power deposition limitations [26]. Multiecho imaging of the heart therefore poses a number of challenges at high field strength.…”
Section: Discussionmentioning
confidence: 99%
“…Although we did not perform a direct comparison between 1.5 Tesla and 3.0 Tesla, other studies have shown improvement in SNR at 3.0 Tesla (Gutberlet et al, 2006;Gutberlet et al, 2004;Lotz et al, 2005;Wittlinger et al, 2005). This increase in SNR from 1.5 Tesla to 3.0 Tesla can be bartered to improve either spatial resolution or temporal resolution as desired for a given application.…”
Section: In Vivo Coronary Artery Studymentioning
confidence: 93%
“…Improvements in spatial resolution and signal-to-noise ratio (SNR) for cardiac imaging applications can be achieved by using higher field strength 3.0 Tesla scanners (Gutberlet et al, 2006;Gutberlet et al, 2004). Validation studies of 3.0 Tesla PC-MRI in larger diameter vessels have recently been performed showing good precision and accuracy at high flow rates (Lotz et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Among the cardiac applications of MR imaging, signal-to-noise (SNR) limited methods such as myocardial perfusion MR (perfusion MR) are most likely to benefit from higher field strength (1)(2)(3)(4)(5)(6)(7)(8)(9). Initial studies have shown improvements in SNR, contrast enhancement and diagnostic accuracy for perfusion MR at 3.0 Tesla compared with 1.5 Tesla (1,2,5).…”
Section: Introductionmentioning
confidence: 99%